An Error Analysis of Students In Writing Sentence on Simple Past Tense - Dinda Sri Fatmawati; Yen Aryni; Putri Lidiana Permata Sari (JURNAL GLOBAL EDUKASI, 2022)
Abstract: The objectives of this research were to find the errors in student’s writing at The Tenth Grade Science 1 of SMA Swasta Daerah Kisaran. The subject of this research were 20 students of SMA Swasta Daerah Kisaran. The technique of collecting data used in this research were interview, observation and written test. The researcher used Dulay’s Theory to classify the types of errors. In this research, the researcher found 4 types of errors. Those were ommision, addition, misformation and misordering. The precentage of frequency the errors. It was ommison type (42,86%), addition type (5,71%), misformation type (22,86%), and misordering type (28,57%). From all of the types, the highest frequent types of error was omission. Keywords: Simple Past Tense Sentence, Writing, Errors Abstrak: Penelitian ini bertujuan untuk menemukan kesalahan dalam menulis siswa kelas X IPA 1 SMA Swasta Daerah Kisaran. Subjek penelitian ini adalah 20 siswa SMA Swasta Daerah Kisaran. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi dan tes tertulis. Peneliti menggunakan Teori Dulay untuk mengklasifikasikan jenis-jenis kesalahan. Dalam penelitian ini, peneliti menemukan 4 jenis kesalahan. Yaitu penghilangan, penambahan, salah formasi dan salah urut. Persentase frekuensi kesalahan. Yaitu tipe omission (42,86%), tipe penambahan (5,71%), tipe salah formasi (22,86%), dan tipe salah susun (28,57%). Dari semua jenis tersebut, jenis kesalahan yang paling sering terjadi adalah omission. Kata kunci: Kalimat Simple Past Tense, Penulisan, Kesalahan